Macrophage migration inhibitory factor promotes breast cancer metastasis via activation of HMGB1/TLR4/NF kappa B axis. Issue 2 (1st June 2016) - Lv, Wei; Chen, Na; Lin, Yanliang; Ma, Hongyan; Ruan, Yongwei; Li, Zhiwei; Li, Xungeng; Pan, Xiaohua; Tian, Xingsong
Highlights: TLR4 was required for MIF-mediated migration of breast cancer cells. MIF-induced ROS generation promoted breast cancer cell migration. MIF regulates breast cancer cell migration via the ERK/HMGB1/TLR4/NF-κB pathway. MIF promoted secretion of cytoplasmic HMGB1 by activating caveolin-1. MIF overexpression enhanced lung metastasis of breast cancer in vivo. Abstract: Macrophage migration inhibitory factor (MIF) is up-regulated in diverse solid tumors and acts as the critical link between immune response and tumorigenesis. In this study, we demonstrated that MIF overexpression promoted migration of breast cancer cells by elevating TLR4 expression. Further investigation evidenced that MIF induced ROS generation. MIF-induced ROS led to ERK phosphorylation, which facilitated HMGB1 release from the nucleus to the cytoplasm. MIF overexpression also induced caveolin-1 phosphorylation. Caveolin-1 phosphorylation contributed to HMGB1 secretion from the cytoplasm to the extracellular matrix. The extracellular HMGB1 activated TLR4 signaling including NF-κB phosphorylation, which was responsible for the transcription of Snail and Twist as well as MMP2 activation. Furthermore, MIF-induced caveolin-1-dependent HMGB1 secretion might control the recruitment of CD11b+ immune cells. Our data suggested that MIF affected the intrinsic properties of tumors and the host immune response in tumor microenvironment by regulating the TLR4/HMGB1 axis, leading to metastasis of breast cancer.